Assessment of knowledge and practice of menstrual hygiene among school going adolescent girls in an urban area of Odisha: a cross sectional study - Pradhan, Sasmita; Kar, Krishna; Samal, Barada Prasanna; Pradhan, Jagannath (International Journal Of Community Medicine And Public Health, 2019)
Background: In the life of a female, menarche denotes the beginning of her reproductive capacity. Menstrual hygiene is an issue that every girl has to deal with in her life, but there is lack of awareness on the process of menstruation, the physical and psychological changes associated with puberty and proper requirement for managing menstruation. Methods: A cross-sectional study was conducted from October 2016 to December 2016 in the urban field practice area of SCB Medical College. One government high school and one private high school were selected purposively. A purposeful convenience sampling was done to select the girls who were studying in 8th, 9th and 10th standard. Data collected from 165 adolescent school girls using a predesigned, pretested and structured questionnaire. The objective of the present study is to assess the knowledge and practices regarding menstrual hygiene among school going adolescent girls and to know about the restrictions imposed upon them during menstruation. Results: Most of the adolescent girls (61.82%) had attained menarche between 13-15 years of age. 59.39% girls were aware about menstruation before menarche. The source of information about menstruation was the mother or elder sister in most of the girls (81.21 %), followed by teachers/friends in case of 18.79 % girls. 84.85% of the girls used only sanitary pad, 4.24% used only cloth and the rest 10.91% used both sanitary pad and cloth during menstruation. Conclusions: Maintenance of menstrual hygiene was better in private school girls as compared to government school girls. Health education sessions about menstrual hygiene should be conducted in the schools for spreading awareness regarding menstruation and menstrual hygiene.